KONTEKSTUALISASI HADITS MENANAM POHON TERHADAP FENOMENA DOOMSDAY NEWS - Ayu Annisa; Emilia Sari (Al-Dirayah, 2022)
This study aims to contextualize the hadiths that talk about the importance of planting trees, butin this case the authors link it to the context of dealing with the Doomsday News phenomenon.Refers to the dissemination of information that often describes a doomsday situation or animpending catastrophe. Although the hadith does not specifically address this phenomenon,there is relevance that can be explored for planting trees as a response to people's concernsabout an uncertain future. This study uses a qualitative approach by analyzing hadiths andrelated literature which provide insights about the Doomsday News. Data was collected througha literature study of hadith books as well as relevant religious literature through the social,historical, and religious background of the hadith and contextualized to society. The results ofthis study are expected to provide an in-depth understanding of the message contained in thehadith with the Doomsday News phenomenon. This research can provide practical guidance forthe community in dealing with anxiety and uncertainty regarding the future, by prioritizingenvironmental values. As well as being able to contribute to religious understanding regardinghuman responsibility in providing a more holistic view when facing frightening news about thefuture. In addition, this research can also be a basis for further research on the relationshipbetween religion, the environment, and actual social issues.